Transtorno do déficit de atenção/hiperatividade: elaboração de material de psicoeducação para crianças - Kojo, Josiane Teixeira da Silva (2022)
In the adequate and continued treatment of ADHD, psychoeducation has a fundamental role, since it works with the provision of clear and relevant information to patients and families. When it comes to the care of children with ADHD, there is a lack of research on this topic aimed exclusively at children. The objective of this study was to develop a written and illustrated material for the psychoeducation of ADHD, to be used by children aged between 06 and 10 years. The study was characterized as an applied research, carried out through data collection, thus, we opted for mixed procedures that seek the integration between qualitative and quantitative data, being divided into three stages: elaboration of a checklist of behavioral goals; application of the behavioral goals checklist to parents of children with ADHD and specialist professionals from different areas who work with this specific audience and, finally, the elaboration of psychoeducation material. After analyzing the data and based on them, a children's book called "I want, I can, I can: Psychoeducation for children with Attention Deficit Hyperactivity Disorder" was produced to serve as a support tool for children, offering the necessary support in the orientation and care related to ADHD, aiming beyond the quality of life, the well-being of the same.